Kinesio Elastic Theurapeutic Tapping (ETT) terhadap Intensitas Nyeri Punggung pada Ibu Hamil Trimester III Berdasarkan Standar Profesi Bidan - Yusita, Intan; Winengsih, Ecih (Universitas Batanghari Jambi, 2025)
The aim of this study was to determine the effectiveness of providing Kinesio Taping in reducing the scale of lower back pain in third trimester pregnant women. The type of research used is Quasi Experimental (quasi-experiment) with a non-equivalent research design pre and post test control group design. The research population was pregnant women in the third trimester who had an examination in the Cikancung Community Health Center Work Area and felt back pain. The sampling technique in the research used a purposive sampling method and the sample size was 36 people. The instruments used in this research used observation sheets, NRS (Numeric Rating Scale), kinesio tapping. The analysis test used was the Wilcoxon Sign Rank analysis test. The results of the study found that there was a change in lower back pain between pretest (before administering Kinesio) and posttest (after administering Kinesio). This shows that the application of pregnancy exercises has a significant influence in reducing lower back pain in pregnant women.